Differences and similarities between sublingual immunotherapy of allergy and oral tolerance. (April 2017) - Moingeon, Philippe; Mascarell, Laurent
Highlights: The buccal and gut immune systems are similarly organized, with a bias toward tolerance induction due to the capacity of resident dendritic cells and macrophages to elicit regulatory T cell responses. Sublingual immunotherapy is established as a treatment for allergic rhinoconjunctivitis, and is being further evaluated as a therapeutic option in asthma and food allergies. Oral immunotherapy is actively investigated as a therapeutic option in food allergies, with current evidence for patient desensitization, but a residual need to achieve true ( i.e., long term) tolerance induction. Abstract: Allergen immunotherapy is the only treatment altering the natural course of IgE-mediated allergies. Whereas the subcutaneous route for immunotherapy (SCIT) has been historically considered as a reference, we discuss herein the relative advantages of the sublingual and oral routes as alternatives to SCIT in order to elicit allergen-specific tolerance. The buccal and gut immune systems are similarly organized to favor immune tolerance to antigens/allergens, due to the presence of tolerogenic dendritic cells and macrophages promoting the differentiation of CD4 + regulatory T cells. Sublingual immunotherapy (SLIT) is now established as a valid treatment option, with clinical efficacy demonstrated in allergic rhinoconjunctivitis (to either grass, tree, weed pollens or mite allergens) and encouraging results obtained in the management of mild/moderate allergic asthma. While still exploratory, oral immunotherapy (OIT) has shown promising results in the desensitization of patients with food allergies. We review at both biological and clinical levels the perspectives currently pursued for those two mucosal routes.